Role of ADDUCIN Gly460Trp, ACE I/D and AGT M235T Gene Polymorphisms in Genetic Susceptibility to Diabetic Nephropathy - Sancakdar, Enver; Ates, Kadir; Kaman, Dilara; Deveci, Koksal; Ozkan, Yusuf; Ilhan, Necip (Modestum Ltd, 2015)
Diabetes mellitus is a metabolic disease with a high incidence of morbidity and mortality lowering the quality of life with acute and chronic complications and it needs to be followed up and treated throughout the lifespan. Concordant with the frequency of DM and the increase in the length of life frequency of DNP is also increased. The I allele of the ACE I/D polymorphism, AGT M235T's T allele and ADD G460W's W allele presence are purported to present a predisposition to DNP. In our study we aimed to investigate the effect of the AGT M235T, ACE I/D and ADD 460W polymorphisms in the development of DNP in patients with diabetes mellitus. The study group consisted of 194 patients with Diabetic nephropathy and the control group contained 100 DM patients. In the diabetic group the DD genotype of the ACE I/D polymorphism was 54 (54.0%) and the D allele was 69.0% and in the nephropathy group II genotype of the ID were 78 (40.2%) and 51 (26.3%) and the I allele was 46.4 respectively and the presence of the I allele was associated with the presence of nephropathy. There was no significance between the genotypes in the presence of a coexistence of AGT M235T and ACE I/D polymorphisms between the groups the MD alleles (42%) demonstrated significance in the diabetic and the T/I alleles (28.1) demonstrated significance in the nephropathy group. In the ADD G640W polymorphism on its own, subjects having GG (77.3%) and WW (7.7%) genotypes (p=0.025) might have been predisposed to nephropathy however when in combination with the ACE I/D, the presence of the DD/GG (45%) in the diabetic group and the presence of the ID/GG (29.9%) and II/GG (19.6%) combination in the DNP group were statistically significant. The D/G (64%) alleles were significant in the diabetic and the I/G (36.6) alleles were significant in the DNP groups respectively. As a conclusion we think that the II-ID/GG genotype and the I/G alleles in the presence of the ACE-ADD combination and TT/ID genotype and T/I alleles in the ACE-AGT combination may be effective in the predisposition of the diabetic patients to nephropathy.
Keywords: DM; diabetic nephropathy; ACE I/D polymorphism; AGT M235T polymorphism; ADD G460W polymorphism